Surgical margins of the oral cavity: is 5 mm really necessary? - James Fowler; Yael Campanile; Andrew Warner; Francisco Laxague; Naif Fnais; Kevin Fung; Adrian Mendez; Danielle MacNeil; John Yoo; David Palma; Anthony Nichols (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Squamous cell carcinoma is the most common malignancy of the oral cavity. Primary treatment involves surgical resection of the tumour with a surrounding margin. Historically, the most commonly accepted margin clearance is 5 mm. This distance is controversial, with recent publications suggesting closer margins do not impact local recurrence and survival. The objective of this study is to determine the closest surgical margin that does not impact local recurrence and overall survival. Methods A retrospective review of the London Health Sciences Centre Head and Neck Multidisciplinary Clinic between 2010 and 2018 was performed. Demographic data, subsite, tumour staging, treatment modality, margins, and survival outcomes were analyzed. The primary endpoint was local recurrence free survival. Secondary endpoints included recurrence-free survival and overall survival. Descriptive statistics, as well as univariable and multivariable Cox proportional hazards regression modelling were performed for all patients. Results Four-hundred and twelve patients were included in the study, with a median follow-up of 3.3 years. On univariable analysis, positive margins and margins < 1 mm were associated with significantly worse local recurrence-free survival, recurrence-free survival, and overall survival (p < 0.05), compared to margins > 5 mm. Patients with surgical margins > 1 mm experienced similar outcomes to those with margins > 5 mm. Multivariable analysis identified age of diagnosis, alcohol consumption, pathological tumour and nodal category as predictors of local recurrence free survival. Conclusions Although historical margins for head and neck surgery are 5 mm, similar outcomes were observed for margins greater than 1 mm in our cohort. These findings require validation through multi-institutional collaborative efforts. Graphical abstract